Impact of Safe School Initiative Programme on Academic Achievement of Victims of Insurgency in Secondary Schools in North - East Nigeria - Chinwuba, Mary Adanna; V.O Adikwu; Usman, Matthew B. (MultiTech Publisher, 2024)
Purpose: The purpose of this study was to investigate the Impact of the Safe Schools Initiative programme on the academic achievement of victims of insurgency in Secondary Schools in North-east, Nigeria. Method: This study adopted a descriptive and Ex-post facto survey design. A sample size of 365 male and female SS1 respondents were sampled for the study. The instrument that was used for this study was a self-structured questionnaire developed by the researcher titled Impact of Safe Schools Initiative programme on behaviours and academic achievement questionnaire (ISSIPBAC). The content validity of the questionnaire was done by lecturers from the university of Abuja and the two data from the pilot test was obtained and correlated using Pearson Product Moment Correlation Coefficient (r), to see the similarities or differences of the scores. A reliability Coefficient of 0.87 was obtained. Thus, the instrument was reliable for the study. Descriptive and inferential statistics were employed in data analysis, through Statistical Package for Social Science (SPSS version 25) was used to carry out the analysis of the research data. Findings: The findings revealed that the difference in the academic achievement of students under the Safe Schools Initiative programme in Secondary Schools in North East, Nigeria was more for male respondents than female respondents. The study also showed that the behaviour of students under the programme in Secondary Schools in North East, Nigeria was better in rural respondents than the urban centres. The result indicated that the academic achievement of the students varied as the age increased and the academic achievement of students under the Safe Schools Initiative programme in Secondary Schools in North East, Nigeria was more on urban respondents than the rural centres. Recommendations: Based on the findings, the paper hereby recommends that the age of these students should be considered in teaching. While students of lower ages were more affected by the insurgency in their academic achievement, others such as 16 years and above were less affected. The school counsellors should organize regular psychological checks on these students to make sure they have stable behavioural patterns.